THE ANALYSIS OF HEADLINESE AND TOPIC VALUE OF HEADLINES NEWS IN DAILY ONLINE NEWSPAPER “THE JAKARTA POST” - Suryahadi, R Agus; Solo, Lenny (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
This study investigates the use of Headlinese and the topic value of Headlines News in the daily online news publication